Characterization and structural modification of polysilsesquioxanes for low dielectric constant (k) applications in deep sub-micron devices - Siew, Yong Kong. (2008)
A preliminary study on the thermal stability of different spin-on dielectrics (SODs) has been conducted and it is found that generally organic SODs exhibited lower thermal stability, both in terms of weight loss and the highest allowable temperature, compared to inorganic SODs. On the other hand, thin film characterization and thermal analysis techniques gave evidences which support the notion that the redistribution of Si-0 and Si-ll bonds is the reaction mechanism responsible for the chemical changes induced by heating. Curing of hydrogen silsesquioxane (HSQ) is found to be accompanied by weight loss, dimension change and change in dielectric properties. A three-stage curing model has been proposed based on the data collected.